2006
DOI: 10.1016/j.bbrc.2005.12.098
|View full text |Cite
|
Sign up to set email alerts
|

Diverse range of small peptides associated with high-density lipoprotein

Abstract: High-density lipoproteins (HDL) were examined as potential carriers of small peptides in plasma. HDL purified by density gradient centrifugation was delipidated and fractionated by size-exclusion chromatography under denaturing conditions. By hplc and mass spectrometry, more than 100 peptide components were found in the size range from 1,000 to 5,000 Da. By sequence analysis, peptides were identified as fragments of proteins such as apolipoproteins, fibrinogen, α 1 -proteinase inhibitor, and transthyretin. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 26 publications
(33 reference statements)
1
55
0
Order By: Relevance
“…However, the composition of the peptides in urine is not clearly understood. The lack of analysis of peptides in urine is likely due to the technical difficulty of measuring peptides in the presence of proteins [17]. Singh et al [43] has studied the variety of peptides in urine from patients with renal disease by combined Lowry method (which detects both proteins and peptides) and Bradford method (which detects only proteins) together.…”
Section: Extraction Of the Peptides From Urinementioning
confidence: 99%
See 4 more Smart Citations
“…However, the composition of the peptides in urine is not clearly understood. The lack of analysis of peptides in urine is likely due to the technical difficulty of measuring peptides in the presence of proteins [17]. Singh et al [43] has studied the variety of peptides in urine from patients with renal disease by combined Lowry method (which detects both proteins and peptides) and Bradford method (which detects only proteins) together.…”
Section: Extraction Of the Peptides From Urinementioning
confidence: 99%
“…The results showed that the excretion of peptides decreased in the presence of proteinuric renal disease [43]. However, this method was controversial because other contaminants such as urinary phenols, free amino acids, other endogenous compounds, and common drugs could interfere with the assay [17]. It is well known that urine contains high concentrations of small metabolites such as nucleotides and organic compounds.…”
Section: Extraction Of the Peptides From Urinementioning
confidence: 99%
See 3 more Smart Citations